2020
DOI: 10.53894/ijirss.v3i4.48
|View full text |Cite
|
Sign up to set email alerts
|

The rate of asymptomatic throat carriage of Streptococcus pyogenes and its associated risk factors among Kabul University students

Abstract: Streptococcus pyogenes (S. pyogenes) is the main agent of acute pharyngitis and skin infections that may result in the late complications of glomerulonephritis and rheumatic fever. Infection with streptococcus group A is a global health problem, which is most common in children and adults. This study was conducted to investigate the rate of S. pyogenes throat carriers and its main risk factors among healthy students of Kabul university. In the present study pharyngeal swabs of 260, [155 (59.6%) were male and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 11 publications
0
8
4
Order By: Relevance
“…However, our ndings were in disagreement with the results of a previous study in which the prevalence rate of S. pyogenes carriage among adults was reported at 2-46% in Turkey [8], 9.6% in Philadelphia [9], 15.6% in young adult inhabitants of Wielkopolska, Poland [10], between 11.2 to 34% in India [11], 3.6% among pharmacy students in a university in Cyprus [5], 16.9% in Kabul university [12], and 63% among health community in Australia [20].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, our ndings were in disagreement with the results of a previous study in which the prevalence rate of S. pyogenes carriage among adults was reported at 2-46% in Turkey [8], 9.6% in Philadelphia [9], 15.6% in young adult inhabitants of Wielkopolska, Poland [10], between 11.2 to 34% in India [11], 3.6% among pharmacy students in a university in Cyprus [5], 16.9% in Kabul university [12], and 63% among health community in Australia [20].…”
Section: Discussioncontrasting
confidence: 99%
“…It was found that the number of children in the family was an important risk factor. Students with 1-3 children in the family had a 23-fold higher risk of carrying S. pyogenes than those who (p 0.05), and those students who had 4-6 children in their family, had a 27-fold higher risk of carrying S. pyogenes in their throat than those didn't have any children (p 0.05) [12].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations